2013
DOI: 10.2807/ese.18.15.20453-en
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of novel avian A(H7N9) influenza viruses isolated from patients in China, February to April 2013

Abstract: Novel influenza viruses of the H7N9 subtype have infected 33 and killed nine people in China as of 10 April 2013. Their haemagglutinin (HA) and neuraminidase genes probably originated from Eurasian avian influenza viruses; the remaining genes are closely related to avian H9N2 influenza viruses. Several characteristic amino acid changes in HA and the PB2 RNA polymerase subunit probably facilitate binding to human-type receptors and efficient replication in mammals, respectively, highlighting the pandemic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…However, human infections have now been detected (6). Preliminary analyses showed that the H7N9 viruses that were responsible for this outbreak are novel reassortants (4,7,8). The disease is concerning because most patients have been severely ill. To date, there have been more than 100 confirmed cases of human H7N9 infection in China, including 37 deaths, according to the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…However, human infections have now been detected (6). Preliminary analyses showed that the H7N9 viruses that were responsible for this outbreak are novel reassortants (4,7,8). The disease is concerning because most patients have been severely ill. To date, there have been more than 100 confirmed cases of human H7N9 infection in China, including 37 deaths, according to the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Several adaptive mutations in the polymerase complex of H5N1 have been identified as contributing to more effective replication in mammals [44,88]. Conversely, most zoonotic H7N9 viruses that have been isolated from humans carry unique mutations in their polymerase PB2 enzyme that are absent from strains isolated from birds [19][20][21]. However, several adaptive mutations in PB1, PA, NP, and NEP have been described that are able to compensate for the poor polymerase activity of zoonotic IAVs in human cells [89].…”
Section: Genetic Factors Contributing To Transmissibility and Virulence In Humansmentioning
confidence: 99%
“…Furthermore, the six internal gene segments were most closely related to H9N2 viruses which are enzootic in chickens in China (Gao et al, 2013). This novel H7N9 virus was characterised as a low pathogenicity (LP) AIV (Kageyama et al, 2013) and caused mild or unapparent clinical disease in domestic chickens and ducks (Pantin-Jackwood et al, 2014), although a more severe pathogenesis may occur in turkeys (Slomka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%